DC distribution systems and microgrids - Dragičević, Tomislav; Wheeler, Pat (Engineer); Blaabjerg, Frede (IET energy engineering series, 2018)
The book is divided into three parts - control circuits, power architectures, and real-world applications. The first part comprises seven chapters, which provides a comprehensive overview of different control approaches focused both on local control functions of individual converters. Building upon the set of control oriented chapters, the three chapters in the second part overview several prominent DC microgrid architectures. Architectures that are different and more complex compared to the most conventional single bus structure were intentionally selected for a detailed overview here, as they can offer additional degrees of flexibility and redundancy. The final part, comprised of seven chapters, presents an analysis of a number of applications in which the control methods and architectures discussed in the first two parts can be applied in the specific context of a given application. The selected applications for this book include aircraft and shipboard systems, electrical vehicles, data centers, residential buildings, and photovoltaic powered systems, respectively. The book ends with an overview of some of the DC microgrid demonstration sites around the world.